Exploring knowledge, attitudes, and practices regarding salt intake: A community-based cross-sectional study - Deepak Sharma; Seema Gupta; Naveen Krishan Goel; Bhavana Katariya; Prabhdeep Singh; Aanchal Sareen (International Journal of Noncommunicable Diseases)
Background: Reducing excessive salt consumption can help mitigate associated health risks. By integrating an understanding of the risks of excessive salt consumption and fostering a positive attitudes toward healthier dietary choices, a low-salt lifestyle can be implemented. Aim and Objectives: To determine the knowledge, attitudes, and practices toward dietary salt intake and to estimate the mean salt intake among adults. Methodology: A community-based cross-sectional study was conducted among 300 study participants in Chandigarh city of North India. After obtaining informed written consent, participants were administered a structured questionnaire. In addition, a spot urine sample was collected from one-sixth of the study participants (n = 50). Data collected were analyzed using Epi Info software for Windows (CDC Atlanta). Results: A high proportion was aware that a high salt diet can cause serious health problems (92.3%). Mostly, the study participants (92.1%) opined that limiting the amount of salt was important for them and 84.7% thought they consumed the right amount of salt. Around two-third (72.2%) of the study participants never/rarely added salt to food at the table and 86.3% took some action to control their salt intake. Among the 50 study participants whose spot urine was tested in 42 (92%), the daily salt intake was more than the World Health Organization (WHO) recommended 5 g/day. Conclusion: The results of this study highlight a high level of knowledge, attitude, and practice with regard to salt intake. However, urine testing revealed that a high proportion of those tested consumed nearly double the WHO recommended threshold of 5 g of salt per day. It is therefore suggested that public health initiatives aimed at promoting recommended salt consumption levels should be further strengthened.